2017
DOI: 10.3183/npprj-2017-32-03-p324-335
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chemical additives on the strength, stiffness and elongation potential of paper

Abstract: The effects of wet-end additions of cationic starches and/or carboxymethyl cellulose (CMC) on paper properties was determined by papermaking trials. The aim of this study was to mitigate the distinctive decrease in strength and stiffness due to unrestrained drying by addition of wet-end additives, while maintaining the extraordinarily high stretch potential of papers after unrestrained drying. Addition of the different polysaccharides increased the tensile index and density of the paper. The largest incgtrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 38 publications
0
24
0
1
Order By: Relevance
“…Examples of mechanical treatments include creping, which can result in elongation of 15-300%, compaction, which increases elongation by up to 10-15%, and patterning of the paperboard with a creaser (Vishtal and Retulainen 2012;Panthi 2016). Strand et al (2017) studied the effect of wet-end additives on paper elongation and found that certain combinations of carboxymethyl cellulose and cationic starch helped to maintain paper elongation after unrestrained drying, although the studied polysaccharides had only a very small effect on elongation if restrained drying was used. Recent findings suggest that MFC improves paper elongation.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of mechanical treatments include creping, which can result in elongation of 15-300%, compaction, which increases elongation by up to 10-15%, and patterning of the paperboard with a creaser (Vishtal and Retulainen 2012;Panthi 2016). Strand et al (2017) studied the effect of wet-end additives on paper elongation and found that certain combinations of carboxymethyl cellulose and cationic starch helped to maintain paper elongation after unrestrained drying, although the studied polysaccharides had only a very small effect on elongation if restrained drying was used. Recent findings suggest that MFC improves paper elongation.…”
Section: Introductionmentioning
confidence: 99%
“…One of the effective ways to increase the strength of cardboard and paper products from waste paper is the addition of chemical auxiliaries to a fibrous suspension. Starches, especially cationmodified, carboxymethyl cellulose, liquid glass and synthetic polymers, such as cationic polyacrylamides and high-molecular polyvinyl amine [8][9][10], are used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of water moving with the polyelectrolyte can be quite substantial, if the polyelectrolyte forms extended loops, trains, or tails. It was previously shown that adsorbed layers of CMC and these cationic starches onto nanocellulose surfaces contained between 52 and 66% of coupled water by weight at adsorption equilibrium (Strand et al 2017). Cationic starches with high DS onto cellulose surfaces results in a significantly more rigid layer, compared to cationic starches with a low DS, because polyelectrolytes with high DS are more strongly attracted to surfaces of opposite charge.…”
Section: Particle Countmentioning
confidence: 99%
“…Adsorption studies using QCM-D and SPR techniques have revealed that polyelectrolytes adsorb differently depending on their chemical properties, such as molar mass and charge density, onto model cellulose or silica surfaces (Tammelin et al 2004;Kontturi et al 2008;Strand et al 2017). A polyelectrolyte with a high charge density will adsorb as a stiffer and more rigid layer, compared to a polyelectrolyte with a low charge density (Kontturi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation